Jatio Sangsad Bhaban or National Assembly Building and Sustainability - Choudhury, Bayezid Ismail (Journal of Engineering Science, 2020)
Designed by American architect, Louis I. Kahn, the Jatio Sangsad Bhaban (JSB) or National Assembly Building of Bangladesh is a world-renowned iconic building situated in Bangladesh. Louis I. Khan was commissioned to design the JSB during the period before the term ‘sustainable’ was coined. In sustainable term it has controversial standing due to its cost, social and participatory aspects. However, it still stands as one of the masterpieces that represent hope and aspiration of the people of Bangladesh. This paper intends to look at the JSB through the lens of ‘sustainability’ to ascertain the degree of sustainability it has or has not achieved considering three tenets of sustainability, namely environmental, social and economic. Journal of Engineering Science 11(2), 2020, 127-132